(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Road safety can be substantially improved by the deployment of wireless communication technologies for vehicular networks, which enables new services and further facilitates communication among moving vehicles. In this paper, we study the performance of vehicular communication systems under various conditions by using MATLAB simulation. Then we improved the performance of the system by employing LMS equalization, which reduced the error and obtained higher data transfer rates. A multipath time-varying channel model with a 100 ns delay spread is used in the simulation. The OFDM system is applied in this paper according to the IEEE 802.11p standard. BPSK, QPSK, 16-QAM, and 64-QAM modulation schemes are used. Which is then combined with a time interleaver and a convolutional encoder. An LMS decision feedback equalizer is used to reduce the impact of inter symbol interference. The decoder utilizes the Viterbi algorithm in order to decode the received signal. A comparison between IEEE802.11p and IEEE802.11a standards has been created to investigate which is more suitable for vehicular communication systems. The performance of different modulation schemes and coding rates for SNR in the range of (0-16) dB was investigated. Then the simulation model has been improved by using LMS equalization and comparing the results of the model with and without the LMS equalizer for different frame sizes and different vehicle velocities. Throughput measurement was used to study system performance in the range of SNR (0-16) dB for unpunctured QPSK over time variant channel with different velocities and different frame sizes. A compression of previous work was executed to show the enhancement that is obtained in this work. The best BER obtained at 50 km/h vehicle speed is 4.3 10-4 at a SNR of 16 dB by using an unpunctured QPSK modulation scheme and an LMS algorithm with (0.01) and 10 frame size.